Non-recurrent SEPT9 duplications cause hereditary neuralgic amyotrophy. Issue 9 (25th November 2009) - Collie, A M B; Landsverk, M L; Ruzzo, E; Mefford, H C; Buysse, K; Adkins, J R; Knutzen, D M; Barnett, K; Brown, R H; Parry, G J; Yum, S W; Simpson, D A; et al.
Abstract : Background: Genomic copy number variants have been shown to be responsible for multiple genetic diseases. Recently, a duplication in septin 9 ( SEPT9 ) was shown to be causal for hereditary neuralgic amyotrophy (HNA), an episodic peripheral neuropathy with autosomal dominant inheritance. This duplication was identified in 12 pedigrees that all shared a common founder haplotype. Methods and results: Based on array comparative genomic hybridisation, we identified six additional heterogeneous tandem SEPT9 duplications in patients with HNA that did not possess the founder haplotype. Five of these novel duplications are intragenic and result in larger transcript and protein products, as demonstrated through reverse transcription-PCR and western blotting. One duplication spans the entire SEPT9 gene and does not generate aberrant transcripts and proteins. The breakpoints of all the duplications are unique and contain regions of microhomology ranging from 2 to 9 bp in size. The duplicated regions contain a conserved 645 bp exon within SEPT9 in which HNA-linked missense mutations have been previously identified, suggesting that the region encoded by this exon is important to the pathogenesis of HNA. Conclusions: Together with the previously identified founder duplication, a total of seven heterogeneous SEPT9 duplications have been identified in this study as a causative factor of HNA. These duplications account for one third of the patients in our cohort, suggesting that duplications of various sizes within the SEPT9 gene are a common cause of HNA.